Wireless World in 2050 and Beyond: A Window into the Future! - Prasad, Ramjee; Dixit, Sudhir; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book gathers visionary ideas from leading academics and scientists to predict the future of wireless communication and enabling technologies in 2050 and beyond. The content combines a wealth of illustrations, tables, business models, and novel approaches to the evolution of wireless communication. The book also provides glimpses into the future of emerging technologies, end-to-end systems, and entrepreneurial and business models, broadening readers' understanding of potential future advances in the field and their influence on society at large.
Introduction -- Technology advancements in 2050 and a prediction of the world beyond 2050 -- Beyond the next generation access -- Ubiquitous wireless communications beyond 2050 -- Networking without networking -- Overcoming the complexity of beyond 2050 Internet of Things networks -- Device-free RF-based sensing beyond activity recognition and localization -- Perspectives on enabling technologies for intelligent wireless sensor networks -- Energy efficient joint antenna techniques for future mobile communication -- Role of Ultra Near-field (i.e., Human Bond Communication) in 2050 and beyond -- Advances in cyber security meet communications requirements in 2050 and beyond -- Access security and personal privacy in public cellular communication systems: The past, present and beyond 2020 -- Re-think tomorrow's car: The convergence of automotive and IoT -- The future of healthcare driven by Sensor and analytics -- Big data and Internet of Things - challenges and opportunities for accelerated business development beyond 2050 -- Defining the ICT strategies for beyond 2050 -- A futuristic multi business model innovation approach to integrate and exploit the synergies across business units -- Challenges and opportunities for wireless in wildlife conservation in human dominated landscapes -- Summary and conclusions -- Index.
Keywords: Telecommunication; Application software; User interfaces (Computer systems).; Human-computer interaction; Technological innovations; Computers and civilization; Communications Engineering, Networks; Computer and Information Systems Applications; User Interfaces and Human Computer Interaction; Innovation and Technology Management; Computers and Society